2017
DOI: 10.1039/c6ta10824e
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcysteine-functionalized microporous conjugated polymers for potential separation of uranium from radioactive effluents

Abstract: For the first time, functional microporous conjugated polymers were synthesized for the efficient separation of uranium from simulated radioactive effluents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 50 publications
5
59
0
Order By: Relevance
“…Therefore, ways have been developed to turn monomers microstructures of the materials or develop their surface oleophilicity and hydrophobility by modifying some hydrophilic groups for wastewater treatment . For example, Han et al reported N ‐acetylcysteine (NAC)‐modified CMPs through a thiol‐yne click reaction, which were found to have good adsorption capacity for separation of uranium from radioactive effluents because of the improved hydrophilic nature. Xu et al developed a strategy for highly efficient removal of uranium (VI) iron using a CMP bearing ethylphosphate ligands (CMP‐EP) as a hydrophilic sorbent from simulated high‐level wastes (HLWs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, ways have been developed to turn monomers microstructures of the materials or develop their surface oleophilicity and hydrophobility by modifying some hydrophilic groups for wastewater treatment . For example, Han et al reported N ‐acetylcysteine (NAC)‐modified CMPs through a thiol‐yne click reaction, which were found to have good adsorption capacity for separation of uranium from radioactive effluents because of the improved hydrophilic nature. Xu et al developed a strategy for highly efficient removal of uranium (VI) iron using a CMP bearing ethylphosphate ligands (CMP‐EP) as a hydrophilic sorbent from simulated high‐level wastes (HLWs).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ways have been developed to turn monomers microstructures of the materials or develop their surface oleophilicity and hydrophobility by modifying some hydrophilic groups for wastewater treatment. 27,28 For example, Han et al 29 reported N-acetylcysteine (NAC)-modified CMPs through a thiol-yne click reaction, which were found to www.soci.org W Wang et al…”
Section: Introductionmentioning
confidence: 99%
“…1 However, the development of the nuclear industry may result in problems related to the discharge of radioactive nuclear wastewater. [2][3][4] Uranium is considered to be one of the most important pollutants in wastewater from the nuclear industry; it is harmful to the environment and human health due to its radioactivity and chemical toxicity. 5 Uranium concentrations in the discharge from uranium ore mining and from abandoned mines reach hundreds of mg L À1 to several mg L À1 , while the values in low-level radioactive wastewater are even higher than tens of mg L À1 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the unique structures, porous organic polymers might be developed as adsorbing materials, which can promote the absorbing ability . They play important roles in catalyzing, environmental protection and remediation, gas adsorption and storage and so on. Han et al .…”
Section: Introductionmentioning
confidence: 99%
“…They play important roles in catalyzing, environmental protection and remediation, gas adsorption and storage and so on. Han et al . have prepared radio‐resistant microporous conjugated polymers for adsorption and separation of uranium from radioactive effluents.…”
Section: Introductionmentioning
confidence: 99%